Association of Lung Consolidation Depth With Pathogens Isolated From Bronchoalveolar Lavage Fluid in Calves With Clinical Signs of Respiratory Disease - Justine Clinquart; Thomas Lowie; Stan Jourquin; Jade Bokma; Bart Pardon (Journal of Veterinary Internal Medicine)
ABSTRACT Background The depth of lung consolidation (≥ 1 and ≥ 3 cm) on thoracic ultrasonography (TUS) is increasingly used as a criterion for antimicrobial treatment. However, its association with bacterial infections remains unclear. Objectives To investigate the associations of clinical and ultrasonographic findings, particularly consolidation depth, with opportunistic bacterial infections (OBI), viral infections, or Mycoplasma bovis (also known as Mycoplasmopsis bovis) infections. Different definitions of OBI were explored, based on various combinations of bacterial species, with or without a neutrophilic profile on cytology. Animals Eighty‐six group‐housed calves with at least one clinical sign of respiratory disease from 19 herds experiencing a respiratory epidemic. Methods Cross‐sectional study. A physical examination, TUS, and non‐bronchoscopic bronchoalveolar lavage were performed. The definitions of OBI were based on semi‐quantitative culture results and cytology. Results Calves with consolidations of ≥ 0.5 cm had higher odds of having an OBI considering most definitions, on M. bovis isolation (odds ratio [OR] = 57.3; 95% confidence interval [CI] = 1.5–2300; p = 0.03) and isolation of a bacterial agent in general (OR = 15.5; 95% CI = 2.3–100; p = 0.01). Animals with consolidation ≥ 1 cm had higher odds of OBI considering all definitions, virus isolation (OR = 15.6; 95% CI = 1.0–240; p = 0.05) and isolation of a bacterial agent in general (OR = 6.9; 95% CI = 1.7–28; p = 0.01). Consolidation ≥ 3 cm, cough, and the California score were not significantly associated with OBI, M. bovis, or both. Conclusion In herds experiencing a respiratory epidemic, consolidation depths ≥ 0.5 and ≥ 1 cm might indicate respiratory disease with a bacterial component.